2007
DOI: 10.1021/ja068875m
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Chain-to-Chain Tunneling in Metal−Alkanethiol−Metal Junctions

Abstract: Intermolecular chain-to-chain tunneling in metal−alkanethiol−metal junctions was investigated by measuring the molecular-tilt dependence of the tunneling through a molecular ensemble of alkanethiols using conducting atomic force microscopy. A variable tip-loading force was applied to tilt the molecular configuration while measuring the current−voltage characteristics of the molecular junctions. The observed transport through the molecules exhibited a tilt angle dependent intermolecular charge transfer in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 16 publications
5
97
0
Order By: Relevance
“…To these histograms, we fitted Gaussian curves using a non-weighting algorithm to avoid biasing the data due to outliers. 69 Statistical Analysis of log(|J|) Rather than J: As noted previously by us 22,23 and others, 43,66,67,86 J is log-normally distributed, rather than normally distributed -that is, log(|J|) is (approximately) normally distributed. We chose, therefore, to plot and fit histograms of log(|J|), rather than J.…”
Section: Management Of Measurement Variabilitymentioning
confidence: 85%
“…To these histograms, we fitted Gaussian curves using a non-weighting algorithm to avoid biasing the data due to outliers. 69 Statistical Analysis of log(|J|) Rather than J: As noted previously by us 22,23 and others, 43,66,67,86 J is log-normally distributed, rather than normally distributed -that is, log(|J|) is (approximately) normally distributed. We chose, therefore, to plot and fit histograms of log(|J|), rather than J.…”
Section: Management Of Measurement Variabilitymentioning
confidence: 85%
“…Because of the large number of measurements possible, this technique provides robust statistical analysis of the conductance data, and histograms of the conductance evolution during breaking show evidence of the formation of molecular junctions. [58][59][60][61][62][63][64][65][66][67][68] In CP-AFM, [69][70][71][72][73][74][75][76] the metal-coated tip, acting as the top electrode, is gently brought into direct contact with the molecules on a conducting substrate, acting as the bottom electrode (this process is monitored by the feedback loop of the AFM apparatus) while an external circuit is used to measure the current-voltage characteristics (Figure 4 b).…”
Section: Break Junctionsmentioning
confidence: 99%
“…Here the intermolecular tunneling had been studied also for elastic process, where the conductivity of a SAM sample was measured with a conductive AFM [33,129,130]. It was reported that the conductivity of alkanethiol SAMs increased with increasing the tilt angle of molecules [33,129,130].…”
Section: Intermolecular and Intramolecular Tunnelingmentioning
confidence: 99%
“…It was reported that the conductivity of alkanethiol SAMs increased with increasing the tilt angle of molecules [33,129,130]. In order to understand this observation, Frederiksen et al, performed the first principles calculation for SAMs by changing the density of alkanethiol molecules on a substrate while keeping the SAM structure [130].…”
Section: Intermolecular and Intramolecular Tunnelingmentioning
confidence: 99%